The writer-reader interaction in publicistic style: a qualitative analysis of the editorial - Šlepikienė, Rūta; Linkevičienė, Nijolė (Lietuvių kalba, 2013)
The paper investigates writer-reader relationships in the Lithuanian press exploring the genre of the editorial. The pilot study aims to answer the question whether the expression of author stance depends on the type of the publication and the topic of the article. The study is based on 22 randomly selected editorials published between 2010 and 2012 in two different types of publications: the daily "Lietuvos rytas" and the weekly "Moters savaitė". The study indicated that the addressee, the way of expressing author stance and the interaction between the addressee and the addresser significantly differ depending on the type and purpose of the publication. A typical addressee of the "Lietuvos rytas" is a middle-aged, socially active, educated person interested in all fields of the public sphere, whereas a typical addressee of the "Moters savaitė" is a middle-aged woman, concerned about the well-being of herself and her family, interested in health matters, family values, and household issues. The addresser of the "Lietuvos rytas" typically represents himself as an expert of a certain subject. Eventhough the author aims at creating a close rapport with readers frequently employing the inclusive we, it is evident that there is no equal relationship between the addressee and the addresser. The author uses convincing strategies: selecting a fairly personal tone, he tries to involve readers into argumentation and guide them to a particular interpretation. Conversely, the addresser of the "Moters savaitė" attemps to create an equal relationship with the reader, and the link between the addressee and the addresser is much more intimate and dialogic. The paper also offers some further insights based on the qualitative analysis of the data.